"Rape Culture" language and the news media: contested versus non-contested cases = Le langage de la culture du viol et les médias d’information: cas non contestés vs cas contestés - Cobos, April (2014)
The American news media has recently reported on several rape and sexual assault cases in various cultural settings, sparking public conversations about rape culture in different cultural contexts. The article is focused as a Critical Discourse Analysis that compares the language use in news articles from The New York Times and The Wall Street Journal over a six months period in order to more clearly understand the way the news media uses language in regards to gender and sexual assault and creates a spectrum of valid versus contested reports of sexual assault in different cultural settings.